The efficacy and implementation of AKL-T01 digital therapeutic in management of attention-deficit/hyperactivity disorder (ADHD) in children: A rapid review of recent evidence: AKL-T01: Efficacy and implementation in ADHD - Khateri, Avin; Afshar, Maziar (Chronic Diseases Journal, 2025)
BACKGROUND: Attention-deficit/hyperactivity disorder (ADHD) is a prevalent neurodevelopmental disorder, often inadequately addressed by conventional treatments. Digital therapeutics (DTx) like AKL-T01 (EndeavorRx), a video game-based intervention, have emerged as innovative alternatives for improving attentional control. This rapid review synthesizes recent evidence on the efficacy and implementation of AKL-T01 in managing ADHD across diverse populations. METHODS: This rapid review involves a systematic search of PubMed, Scopus, and Web of Science (2020-2023) which identified 127 records, with 122 excluded during screening (78 irrelevant, 44 non-English/non-peer-reviewed). Five studies evaluating AKL-T01 were included. Outcomes included attentional performance [Test of Variables of Attention (TOVA) Attention Performance Index (API)], ADHD symptoms, and usability metrics. RESULTS: Across 1516 participants, AKL-T01 demonstrated significant improvements in objective attention measures [mean TOVA effect size: 0.5 standard deviation (SD) versus methylphenidate’s: 1.0 SD], particularly in pediatric populations. Parent-reported outcomes showed mixed results. Compliance rates averaged 83%-96%, with minimal adverse effects. CONCLUSION: AKL-T01 shows promise as a safe, adjunctive DTx for pediatric ADHD. Ethical considerations (e.g., data privacy, neurodiversity-affirming frameworks) and long-term efficacy require further study.